Formative research and scientific production of Peruvian dental faculty - Luna-Mazzola, Ivo (2022)
Formative research together with scientific teaching production are very early ways of teaching the research process, which implies the research culture that must be established from the undergraduate level, taking into account its purpose, which is the dissemination of knowledge generated through scientific publication, for which it must seek to overcome the main obstacles that faculty scientific production presents. In the Peruvian universities that teach dentistry, formative research has been promoted to strengthen future research in the field of health sciences, being the faculty scientific production of utmost importance for the contribution to the advancement of science and implication of the students with that cause. The aim of this paper is to reflect on some aspects of faculty scientific production and formative research in Peruvian dental schools.